Mathematical model for technical economic analysis for the optimization of pump gravity water supply system - Taseski, Goce; Nikola Krstovski (Savez inženjera i tehničara Srbije, Beograd Za, 2024)
The rapid growth of the price of electricity has led to the need for the management of water supply systems to have a new primary goal, which is the capture of new underground gravity sources of water that are at a relatively greater distance from the existing water supply system, in order to reduce the quantities of water that are provided by pumping. The purpose of this paper is to develop a mathematical model for a technical economic analysis (cost benefit analysis) of an existing water supply system for which an additional gravity source of water is foreseen, where by analyzing the construction costs of the gravity pipeline and the total operating costs of the system such as: maintenance, depreciation and electricity costs, the optimal amount of water that should be taken from the future gravity water source will be determined.
Keywords: combined water supply system, groundwater, costs - benefits, optimization